Association between physical activity and sleep duration among young adults of UiTM Seremban 3 / Muhammad Taufiq ... [et al.]. - Taufiq, Muhammad; Saat, Akif; Najihah, Nur; Naja, Nurun; Sahira, Naimi; Syed Mud Puad, Sharifah Maimunah (2024)
Sleep and physical activity have been shown to be correlated in research, but this association is only correlational and does not show relationships over time. This study aimed to investigate the correlation between physical activity and sleep duration. A total of 26 healthy young adults (age 21.0 ± 2.2 years) participated in this study. The amount of exercise and sleep duration were assessed using a uniaxial accelerometer. There was no significant correlation between total sleep time and calories burned (B = -0.312, p = 0.077), moderate to vigorous physical activity (B = -2.22, p = 0.087), while there is a significant correlation between total sleep time with steps count (B = -0.0267, p = 0.013). The results suggest that there is evidence that physical activity can help in promoting healthier sleep. Other factors that may influence sleep among young adults include diet, daily lifestyle, and sleep routine.